"Dumbbell"‐ and "Clackers"‐Shaped Dimeric Derivatives of Monocarba‐closo‐dodecaborate. Issue 6 (16th January 2018) - Kitazawa, Yu; Watanabe, Mamoru; Masumoto, Yui; Otsuka, Mai; Miyamoto, Kazunori; Muranaka, Atsuya; Hashizume, Daisuke; Takita, Ryo; Uchiyama, Masanobu
Abstract: We designed, synthesized, and characterized two types of dimeric forms of monocarba‐ closo ‐dodecaborate, namely, a "dumbbell"‐shaped dianion having a C−C bond and a "clackers"‐shaped monoanion having an iodonium linker. The unique architectures of these anionic molecules were established by X‐ray analysis. Spectroscopic analysis, DFT calculations, and reactivity experiments revealed high anionic and chemical stability of both anions, which are crucial properties for weakly coordinating anions. Abstract : Weakest link : Coupling of monocarba‐ closo ‐dodecaborate resulted in "dumbbell"‐ and "clackers"‐shaped dimeric derivatives (see picture; purple sphere=iodine). X‐ray analysis established the unique architectures of these anionic molecules. Combined spectroscopic analysis, DFT calculations, and experimental studies revealed their distinctive properties as weakly coordinating anions (WCAs).